2017
DOI: 10.7762/cnr.2017.6.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Effect on 12-week Intensive Dietary and Exercise Program on Weight Reduction and Maintenance in Obese Women with Weight Cycling History

Abstract: This study examined the effect of 12-week intensive dietary and exercise intervention program on body composition and stress-related hormones in obese women and to examine the residual effect after the intervention. The participants of this study were 30 obese women who had a body mass index of over 25 kg/m2 and over 30% in body fat. They were classified into 2 groups depending on the history of weight cycling (WC); the WC group (≥ ±5% of the original body weight) and the non-weight cycling (NWC) group. Both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Significant improvements were observed across most outcome measures which supports the effectiveness of multidisciplinary TOMS intervention improving physical and functional outcomes over the short‐term. The weight reduction of 10% and waist circumference of 10.5 cm observed in this study compares favourably with other studies involving VLED and exercise interventions of similar time frames that demonstrated approximately 10% weight loss and reduction of waist circumference by 8 cm 22,23 . A weight loss of 5% is considered to be clinically meaningful and successful as this elicits changes in risk of type 2 diabetes and coronary artery disease 24 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Significant improvements were observed across most outcome measures which supports the effectiveness of multidisciplinary TOMS intervention improving physical and functional outcomes over the short‐term. The weight reduction of 10% and waist circumference of 10.5 cm observed in this study compares favourably with other studies involving VLED and exercise interventions of similar time frames that demonstrated approximately 10% weight loss and reduction of waist circumference by 8 cm 22,23 . A weight loss of 5% is considered to be clinically meaningful and successful as this elicits changes in risk of type 2 diabetes and coronary artery disease 24 .…”
Section: Discussionsupporting
confidence: 77%
“…that demonstrated approximately 10% weight loss and reduction of waist circumference by 8 cm. 22,23 A weight loss of 5% is considered to be clinically meaningful and successful as this elicits changes in risk of type 2 diabetes and coronary artery disease. 24 Literature on minimal clinically important differences (MCID) regarding improvements in 6MWT and 30 s STS tests is not available for the obese population after a weight loss intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Food habits Vegetarian 1 (5) 0 (0) 1 ( 5 weight [15]. A secondary analysis of Finnish diabetic prevention study to assess the effectiveness of LI on metabolic syndrome also had similar findings; a significant decrease in the prevalence of abdominal obesity, high blood pressure, low HDL and elevated cholesterol in the intervention group [16].…”
Section: Resultsmentioning
confidence: 71%
“…It has been determined that mild and moderate aerobic exercise affects body composition in obese women positively. Kuwon et al (2017) applied simple stretching movements, 30 minute treadmill and 30 minute cycling exercise and dietary restriction to 30 obese women for 12 weeks, 3 days a week for 70 minutes per day with a professional trainer. They found that 12-week exercise and dietary restriction resulted in a significant decrease in BMI values of obese individuals.…”
Section: Discussionmentioning
confidence: 99%